India-Pakistan : themes beyond borders - Edited by Anil Nauriya (New Delhi Aakar books, 2019)
One of the leading journalists of his time, Nikhil Chakravartty (1913-1998) had his ear to the ground and therefore his writings are a treasure-trove for those studying the political processes of the period. He wrote extensively on the subject of India-Pakistan relations. The writings selected in this volume, spanning thirty-three years (1964-1997), cover vital developments in this area like Jawaharlal Nehru's initiative to send Sheikh Abdullah to Pakistan to explore the possibilities of a permanent solution to the Kashmir problem; the conflict between India and Pakistan in 1965 over Kutch; the events leading up to the Tashkent Agreement; the transformations withing East Pakistan resulting in its dissociation from the ruling dispensation of West Pakistan (about which Nikhil Chakravartty had given some indication as early as in 1964); the Bangladesh liberation struggle and the December 1971 war; the Simla talks and the Indira-Bhutto agreement in July 1972; the democratic interlude which followed and the subsequent happenings till the Gujral-Nawaz Sharif parleys that offered possibilities of a positive turn in the bilateral relationship. Nikhil Chakravartty's writings were imbued with perceptions gained from his interactions with prominent decision-makers and common people on both sides of the border.
Keywords: Diplomatic relations; Politics and government